Spatiotemporal analysis of 3D human iPSC-derived neural networks using a 3D multi-electrode array - Lam, Doris; Enright, Heather A.; Cadena, Jose; George, Vivek Kurien; Soscia, David A.; Tooker, Angela C.; Triplett, Michael; Peters, Sandra K. G.; Karande, Piyush; Ladd, Alexander; Bogguri, Chandrakumar; Wheeler, Elizabeth K.; et al. (Frontiers in Cellular Neuroscience, 2023)
There is a growing appreciation for 3D neural tissues and the advances made with 3D multielectrode arrays to detect, with high spatial resolution, 3D neural network activity. Currently, the limiting bottleneck are computational analytical tools to discern region-specific changes within the Z dimension of the 3D tissue. In this study, we introduce a novel computational analytical pipeline to analyze 3D neural network activity recorded from a 'bottom-up' 3D MEA integrated with a 3D hydrogel-based tissue containing human iPSC-derived neurons and primary astrocytes. We describe the development and maturation of 3D neural activity (i.e., features of spiking and bursting activity) within cross sections of the 3D tissue, based on the vertical position of the electrode on the 3D MEA probe, in addition to network activity (identified using synchrony analysis) within and between cross sections. Then, using the sequential addition of postsynaptic receptor antagonists, we evaluated the dependence of networks within and between cross sections of the 3D hydrogelbased tissue to GABA and/or glutamate synaptic transmission. Collectively, this study demonstrates the need for computational tools to provide a greater depth of understanding of the functional 3D network properties within a tissue system being developed or used to understand disease/injury or chemical exposures.